Factors affecting lung cancer stage at diagnosis and receipt of surgery in Ontario: A population-based analysis - Nader M. Hanna; Saad Shakeel; Gileh-Gol Akhtar-Danesh; Noori Akhtar-Danesh; Christian Finley (PLoS ONE, 2026)
Lung cancer is the leading cause of cancer mortality in Canada, with most cases diagnosed at advanced stage. Despite universal healthcare, social determinants of health may impact stage at diagnosis and access to treatment. We examined the association between these factors, stage at diagnosis, and receipt of surgery in Ontario. We conducted a population-based retrospective cohort study of adults diagnosed with lung cancer in Ontario from 2007–2023 using linked administrative health data. Stage was obtained from the Ontario Cancer Registry. Factors included income, primary care attachment, immigration status, geographic region, and distance to the nearest cancer centre. Logistic regression identified factors associated with stage IV diagnosis. Among 106,867 patients with available stage data, 52.6% were diagnosed with stage IV disease; 19.1% were stage I. Patients without a family physician were significantly more likely to present with stage IV cancer compared with those fully rostered (62.1% vs 51.5%; adjusted OR 1.55, p < 0.001). Females had lower likelihood of stage IV diagnosis than males (OR 0.85, p < 0.001). Increasing household income was associated with reduced likelihood of stage IV disease (OR 0.92 for highest vs lowest quintile, p < 0.001). Immigrants were less likely to be diagnosed with stage IV cancer than non-immigrants (OR 0.77, p = 0.001). Frailty was associated with higher odds of stage IV disease (OR 1.01, p = 0.009). Surgical resection was performed in 56.1% of patients with stage I disease and 1.4% with stage IV disease. Receipt of surgery decreased with advancing age (27.0% < 50 years vs 7.3% ≥ 80 years), higher comorbidity burden (25.4% with 0 vs 5.0% with ≥5 comorbidities), and lack of primary care attachment. Marked social inequities in lung cancer stage at diagnosis and surgical treatment persist in Ontario. Interventions addressing primary care attachment and upstream social determinants may improve early detection and access to curative therapy.